Implantación del Sistema Contable en la Empresa SELEC – CAR en la Ciudad de Loja período Enero - Marzo 2013. - Merizalde Cuenca, Stalin Wladimir (2014)
This thesis entitled "Implementation of Accounting System for Business SELECT - CAR in the city of Loja period January to March 2013 dedicated to the marketing of auto parts, I performed with the firm intention of contributing to the needs lacking these businesses, with the ultimate goal of bringing effective control of operations performed and achieving an effective benefit. The development of this thesis is satisfied with the overall objective Implement an Accounting System for Business SELECT - CAR in the city of Loja period January to March 2013 and according to the specific objectives outlined in the project plan accounts was adapted that facilitated the registration, inventory of goods, documents and accounting records was performed; the accounting process is executed to obtain Financial Statements, Financial Ratios applying that helped express the situation of the company. Concluding that the accounting system provided an orderly and systematic information from the Initial Inventory to the financial statements so that the company must take account of that work and continue with it that allows you to achieve real and reliable financial statements for good decision making. With the completion of the accounting process in the company under study found that the organization of it contributes to the correct and accurate decision making for the betterment of the company since as shown in the results the company is working to loss what does not correctly set the selling prices.